Gemilang - Yusof Haslam, Datuk ([S.l.] : Skop Productions [production company] ; Kuala Lumpur : Speedy Video [distributor], 1987)
Sebuah filem Melayu arahan Yusof Haslam
Copy available in DVD format
Skrip, Yusof Haslam ; jurukamera, Jamal Maarif, Omar Ismail ; penyunting, Salehan Shamsuddin
Erra Fazira, Hans Isaac, Ning Baizura, Jalaluddin Hassan
Keywords: Motion pictures -- Malaysia; Malay drama